Robotic Arm controlled using IoT application. (January 2023) - Kareemullah, H.; Najumnissa, D.; Shajahan, M.S. Murshitha; Abhineshjayram, M.; Mohan, Varshan; Sheerin, S. Ayisha
Abstract: Work-from-home policies have been the standard since the worldwide pandemic breakout, and this has spurred the fast development of applications in the area of IoT for remotely monitoring and managing applications. This has encouraged us to design and develop a remotely controlled robotic arm that can be used in applications where the engaging human hazardous environment (such as quarantined rooms of COVID affected patients) is dangerous. This has led to the development of a B-rover called a robotic arm, which the technicians remotely control to reduce the direct contact between the technician and the hazardous environment. It has various applications, such as a health monitoring system for monitoring the patient's health conditions, sample collection from the patients and the capability of the Robotic Arm to deliver medications to the COVID affected patients without engaging humans. It is proposed to design a 3DOF(degrees of freedom) robotic arm with stepper motor which is controlled through Wi-Fi using the BlynkIoT App with widgets like Joystick and Sliders. This will pick and drop the objects from one place to another. The results show that the designed robotic arm shows a 3% variation from the simulated and actual results when the slider is adjusted.